COST CAPACITY FACTOR MODEL DEVELOPMENT FOR BUILDING CONCEPTUAL COST ESTIMATE - Fa-Ati Amelia (NIM 250 04 008), Ayar
Abstract : Capacity factor method is well known and widely used in construction industry of developed countries as a method in estimating construction cost of petrochemical plants, airport and other engineered facilities at their preliminary planning stage. In Indonesia, the use of this method, especially for building construction, is still limited and not well developed compared to other method, i.e., parametric cost estimate that is closely related to building functions. This capacity factor method considers design capacity of a facility in estimating the construction cost at its preliminary planning stage. Standardized minimum capacity of a facility is commonly used by architect to set the design capacity of a facility with a particular function. After collection field research, data is grouped according to building function. The building data in this research is historical data from government offices, elementary schools, and colleges in West Java. The data on each building function is classified according a certain rule to see characteristics of its capacity factor. The building capacity observations in this research are physical capacity and functional capacity according to building function. Based on the classification, capacity and cost will be plotted in algorithm. Analysis method that is used in this research is simple regression. Cost capacity factor is shown by the slope acquired from capacity and cost which have a certain range. The result of this research shows that physical capacity has more influence to office buildings and colleges, whereas functional capacity shown by the number of students has more on elementary school building. Generally, building capacity factor with a value more of than one shows that the cost increase is more than its capacity increase.